Pelatihan Pembuatan Serta Merancang Konsep Affiliate Marketing Content Digital Bisnis Organisasi Menggunakan AI Bagi Ikatan Remaja (IKRAR 007) - Sita Anggraeni; Syaifur Rahmatullah; Achmad Rifai (AMMA : Jurnal Pengabdian Masyarakat, 2025)
The younger generation, also known as Gen-Z, has been familiar with technology from an early age and is more attuned to the rapid pace of technological development. This has enabled the younger generation to easily understand technology and adapt it to their daily lives. Digital marketing has a significant impact on consumers' ease in deciding to purchase a product. With digital marketing, it is hoped that every business owner can develop and expand their business. Content Marketing provides relevant material in print and digital media to the target audience. Therefore, content needs to be tailored to the target market. Affiliate marketing can create digital marketing strategies that utilize affiliate links that are created and distributed to generate revenue from purchases. Affiliate marketing operates on a compensation basis for each sale. For example, when a business or brand sells a product or service, it will automatically be paid or receive a commission, and there will be mutual benefits for affiliates who showcase or promote the product. Members of the Youth Association (IKRAR 007) RW 07 have many positive activities within the organization but lack the skills to attract sponsors in various ways and lack the skills in the concept of creating creative digital affiliate marketing content for businesses that can quickly and accurately target many sponsorships. The purpose of this training is to understand the skills involved in creating digital affiliate marketing content for organizations using AI and to practice the steps involved in creatively developing content concepts that can quickly and accurately attract numerous sponsorships for the administrators and members of the Youth Association (IKRAR 007) RW 07.